Acceptable risk [large type] - Eason, Lynette (Eason, Lynette. Danger never sleeps, 2020)
"Barely back home after being held hostage overseas, journalist Sarah Denning digs for the truth behind her brother's death with the help of former Army Ranger Gavin Black. As her enemies seek to silence her, Sarah and Gavin race to peel back layers of lies so the truth can finally be revealed." --Provided by publisher.